2013
DOI: 10.1109/tap.2013.2283279
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Analysis of Complex Periodic Structures by Full-Wave Solution of Even-Odd-Mode Excitation Problems for Single Unit Cells

Abstract: The Bloch modes of complex periodic structures are computed by superimposing results obtained from even-odd-mode full-wave driven simulations of individual unit cells. In order to emulate the periodic boundary conditions for the Bloch modes, one full-wave simulation is performed with magnetic and one with electric boundary conditions yielding the even-and odd-mode results, respectively. Therefore, the employed full-wave solver does not even need to support periodic boundary conditions. Since the non-periodic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…Certainly, the full-wave simulator employed to characterize the macro-cell does take into account all the possible interactions between adjacent cells (which justifies its identification with a cascade of multi-port equivalent networks). This method has several drawbacks such as the intense computational load required to analyze a macro-cell involving many unit cells (as required in many practical problems) [39,41], the appearance of spurious solutions, and the ambiguity of the phase constant outside the first fictitious Brillouin zone imposed by the repetition of the unit cell [39]. These inherent difficulties have motivated the search for approaches that can overcome them, as for example those reported in [39,41].…”
Section: Methods Of Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Certainly, the full-wave simulator employed to characterize the macro-cell does take into account all the possible interactions between adjacent cells (which justifies its identification with a cascade of multi-port equivalent networks). This method has several drawbacks such as the intense computational load required to analyze a macro-cell involving many unit cells (as required in many practical problems) [39,41], the appearance of spurious solutions, and the ambiguity of the phase constant outside the first fictitious Brillouin zone imposed by the repetition of the unit cell [39]. These inherent difficulties have motivated the search for approaches that can overcome them, as for example those reported in [39,41].…”
Section: Methods Of Analysismentioning
confidence: 99%
“…This method has several drawbacks such as the intense computational load required to analyze a macro-cell involving many unit cells (as required in many practical problems) [39,41], the appearance of spurious solutions, and the ambiguity of the phase constant outside the first fictitious Brillouin zone imposed by the repetition of the unit cell [39]. These inherent difficulties have motivated the search for approaches that can overcome them, as for example those reported in [39,41]. The procedure given in [39] can solve the drawback related to the appearance of spurious solutions at the expense of increasing the computational load.…”
Section: Methods Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Under the assumption that each corrugation can be replaced by Marcuvitz's closed-form equivalent circuit [28], it was easily shown that the glide symmetry effect is equivalent to simply halving the spatial period. The study in [29], discussing reduced representations of several kinds of higher-symmetric periodic lines proposed in [30], has recently shown that a more correct condition for this conclusion is to neglect interactions due to localized excitation of higher-order waveguide modes.…”
Section: Introductionmentioning
confidence: 99%